Evaluation of stimulus intensity fading on reduction of rapid eating in a child with autism. Issue 1 (23rd January 2018) - Valentino, Amber L.; LeBlanc, Linda A.; Raetz, Paige B.
Abstract : This study assessed the effects of a vibrating pager on reduction of rapid eating. The study also evaluated two strategies for fading the pager, by intensity and by frequency. The pager was successful in decreasing the pace of eating to an appropriate level and the pager prompt was successfully faded. Fading by frequency was ineffective in maintaining an appropriate pace of eating while intensity fading was successful.